PHYSICAL QUALITY OF BALI BEEF MARINATED WITH KLANCENG HONEY (Trigona Sp.) - M. A. N., NASUTION; SRIYANI, N. L. P.; WIBAWA, A. A. P. P. (Majalah Ilmiah Peternakan, 2024)
Thei purpose of thisi study is to evaluate the physical quality of Bali beef marinated with Klanceng Honey (Trigo- na Sp.) and establish its optimal influence. The marinating of the beef took place at room temperature for 30 minu- tes. Four treatments and seven replications were used in the fully randomized research design. The four treatments included non-marinated meat (P0); meat marinated with 5 ml of Trigona honey (P1); meat marinated with 10 ml of Trigona honey (P2); and meat marinated with 15 ml of Trigona honey (P3). In this investigation, the following variables were noted: pH level, meat color, cooking loss, raw loss, and water holding capacity. The findings revea- led that marinating Bali beef with Trigona honey significantly affected pH, cooking loss, raw loss, and meat color (P0.05), but had no significantly different impact on water holding capacity (P>0.05). Because the values for pH, DIA, brightness (L*), and redness (a*) have decreased, while the values for cooking loss, raw loss, and yellowness (b*) on meat color have increased, this study concludes that Klanceng Honey (Trigona Sp.) as a marinade for Bali beef has not been able to improve the physical quality of Balii beef.